Voluntary and Coercive Relations in Society. An Outline - Zonik, Joanna; Zonik, Przemysław (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
The article elaborates on two kinds of relations between people that seem crucial to understanding what is the real nature of processes going on in society. First, each of the relations is characterized with cybernetic nomenclature. Then the relations are compared and their intrinsic properties are showed. The last section pictures their consequences for shaping the contemporary society.